Investigation of structural properties of CdS thin films grown by chemical bath deposition technique (Journal of the College of Basic Education, 2022)
Using chemical path technique, thin films of CdS have been prepared with two different thicknesses on a glass substrate. An attempt to relating structure properties of cadmium sulphide (CdS ) thin film with variation of thickness was reported. X-ray diffraction (XRD) was used to characterize the samples. One peak of (111) orientation is appeared in X-ray chart indicating the cubic phase of the films